2005
DOI: 10.1007/s11748-005-0058-y
|View full text |Cite
|
Sign up to set email alerts
|

Oncocytic carcinoid of the lung

Abstract: An U It ras t ru c t u ra I An a I ysis DANIEL SCHARIFKER, MD, AND ALBERT0 MARCHEVSKY, MD A 52-year-old man with a typical carcinoid tumor of the lung in which the tumor cells displayed marked oncocytic metaplasia is presented. The clinicopathologic and ultrastructural differences with so-called oncocytic of the lung are discussed. The potential of Kulchitsky cell derivatives to undergo oncocytic metaplasma is documented ultrastructurally. Cancer 47530-532, 1981. ARCINOIDS OF THE BRONCHUS were first described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…There was no electron microscopic examination in our case. But, it has been reported that immunohistochemical positivity does not have to be specific for this diagnosis (11) unless oncocytic changes are thought to depend on a high number of mitochondria in the cell cytoplasm (16).…”
Section: Discussionmentioning
confidence: 99%
“…There was no electron microscopic examination in our case. But, it has been reported that immunohistochemical positivity does not have to be specific for this diagnosis (11) unless oncocytic changes are thought to depend on a high number of mitochondria in the cell cytoplasm (16).…”
Section: Discussionmentioning
confidence: 99%
“…Oncocytic carcinoid tumors have been reported in the nasopharynx [5], thymus [6], lung, pancreas [7], kidney [8], and urinary bladder [9]. Oncocytic carcinoid tumor of the lung has been reported in 11 single-case reports [10][11][12][13][14][15][16][17][18][19][20] and 1 case in a series analysis of carcinoid tumors [3].…”
Section: Introductionmentioning
confidence: 99%